AWARENESS AND KNOWLEDGE OF COLOR VISION DEFICIENCY AMONG HEALTH CARE STUDENTS WITH INTERVENTION - RISHITHA, YARRAMALA; IKRAM, SYEDA SADIYA; PURI, SANJEEV KUMAR (International Journal of Current Pharmaceutical Research, 2022)
Objective: To assess the level of awareness and knowledge of Color Vision Deficiency and to determine problems related to color vision among health care students. Methods: This study was done on 278 Health care students in the age group of 18 to 25 y. Structured Pre and Post assessment questionnaires were administrated to all consenting students to determine the prevalence of Color Vision Deficiency and a video is shown to assess the level of awareness and knowledge of Color Vision defects. Color Vision was tested by using Ishihara Color Vision Chart. This study was conducted between November 2021 to January 2022. Ethical clearance for the study was obtained from Saveetha College of Allied Health Sciences. Results: A total of 278 subjects participated in this study, 277(99.6%) subjects have a normal level of Color Vision. Around 66.5% of subjects were aware of color vision deficiency in pre-assessment and 100% of subjects were aware in post-assessment, around 99.6% of subjects found no difficulty in choosing colors of clothes, cosmetics, 100% of subjects had no color difficulty in previous and daily work/study activities and among them, one subject (0.35%) could not appreciate color considered as total Color blindness according to the chart used. Conclusion: It is concluded from this study that a large group of students attains a normal level of Color Vision. Most of them (66.5%) are aware of Color Vision deficiency in pre-assessment, after providing them with adequate awareness and knowledge increases to 100% in post-assessment.